Pyogenic liver abscess associated with oral flora bacterium, Streptococcus anginosus in a patient with underlying tuberculosis - Sunite A Ganju; Neha Gautam; Garima Sharma (Wolters Kluwer Medknow Publications, 2017)
Streptococcus anginosus forms a part of the commensal flora of the oral cavity. However, it can be aggressive and may lead to gastrointestinal and urogenital infections. We present an interesting case and course in a 38-year-old immunocompetent female patient with pyogenic liver abscess due to S. anginosus infection who had multiple carious teeth and underlying pulmonary tuberculosis.